High-intensity focused ultrasound ablation as a treatment for benign thyroid diseases: the present and future - Kotewall, Nicholas (Ultrasonography, 2019)
High-intensity focused ultrasound (HIFU) is a promising ablation technique for benign thyroid nodules. Current evidence has found good short- to medium-term outcomes, similar to those of better-established ablation techniques such as radiofrequency and laser ablation. The fact that it does not require insertion of a needle into the target makes HIFU a truly non-invasive treatment. Although it is not without risks, its low risk profile makes it an attractive alternative to surgery. There is much room for future development, starting from expanding the current indications to enhancing energy delivery. Relapsed Graves disease and papillary microcarcinoma are diseases that can benefit from HIFU treatment. Its role in the mediation of immune responses and synergistic effects with immunotherapy are promising in the fight against metastatic cancers.